IncreasMeningkatkan Kompetensi Guru dalam Mendukung Tantangan Keberlanjutan Pengajaran di Era Globaling Teacher Competency in Supporting Teaching Sustainability Challenges in the Global Era - Kusnandi Kusnandi (Journal of Education and Teaching (JET), 2024)
This research aims to explore the role of teacher competence in addressing the challenges of sustainable learning in the era of globalization. The method used is a qualitative approach with a literature review, involving the identification, collection, and analysis of relevant literature from Google Scholar between 2015 and 2023, using the keyword "Teacher Competence." The research findings highlight the urgency of improving teacher quality as the key to overcoming low educational standards in Indonesia. Strengthening teachers' pedagogical, personal, social, and professional competencies is central to enhancing the national education system. The study concludes that bolstering these competencies is a priority for facing sustainable learning challenges, enabling Indonesia to compete globally and produce a qualified generation. The researcher recommends a holistic strengthening of teacher competencies to address global challenges effectively.